pembiasaan PEMBIASAAN MENJAGA KEBERSIHAN GIGI DAN MULUT PADA ANAK MELALUI METODE PERMAINAN BERSAMA TIMMY DAN TOMMY DI SDN 030 RAWA BANGUN RENGAT INDRAGIRI HULU - Yulianto, Yulianto; Deswita, Deswita; Sukma, Dewi Melati; Bahri, Aisyah Amanda; Hardita, Lisha Febrianty; Rifani, Putri Ardila (Poltekkes Kemenkes Riau, 2023)
Dental and oral health is often the umpteenth priority for some people. In fact, as we know, teeth and mouth are the gateways for germs and bacteria to enter so that they can interfere with the health of other organs of the body. (Infodatin, 2017). The problem of cavities is still a lot of complaints by children and cannot be allowed to get worse because it will affect the quality of life where they will feel pain, discomfort, disability, acute and chronic infections, eating and sleeping disorders and have a high risk of being hospitalized. causing high medical costs and reduced time spent studying at school (Elina and Sumiarti, 2016) School-age children are a strategic target for implementing health programs, because apart from their large number, they are also an easy target to reach because they are well organized. The target of this activity is prioritized for elementary schools. This activity was carried out to increase students' knowledge about the importance of maintaining oral and dental hygiene in particular and body health in general. In addition, it aims to get used to maintaining dental and oral hygiene from an early age. (Indonesian Health Profile, 2015). The purpose of this activity is to increase children's knowledge and attitudes in maintaining oral hygiene using the Timmy and Tommy game method at SDN 030 Rawa Bangun Rengat Indragiri Hulu Keywords: habituation, maintaining cleanliness, teeth and mouth, game method